2013
DOI: 10.3174/ajnr.a3437
|View full text |Cite
|
Sign up to set email alerts
|

Should Patients with Autosomal Dominant Polycystic Kidney Disease Be Screened for Cerebral Aneurysms?

Abstract: SUMMARY:Autosomal dominant polycystic kidney disease is a genetic disorder affecting 1 in 1000 people worldwide and is associated with an increased risk of intracranial aneurysms. It remains unclear whether there is sufficient net benefit to screening this patient population for IA, considering recent developments in imaging and treatment and our evolving understanding of the natural history of unruptured aneurysms. There is currently no standardized screening protocol for IA in patients with ADPCKD. Our revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 60 publications
(60 reference statements)
1
35
0
Order By: Relevance
“…A direct comparison of 3T time-of-flight MRA with 64 channel multi-detector CTA showed that these techniques have comparable sensitivity and specificity for detection of IA and can detect IAs as small as 2–3 mm. 5153 MRA is, however, the screening method of choice as gadolinium-based contrast agents are not required.…”
Section: Aysmptomatic Intracranial Aneurysmsmentioning
confidence: 99%
See 2 more Smart Citations
“…A direct comparison of 3T time-of-flight MRA with 64 channel multi-detector CTA showed that these techniques have comparable sensitivity and specificity for detection of IA and can detect IAs as small as 2–3 mm. 5153 MRA is, however, the screening method of choice as gadolinium-based contrast agents are not required.…”
Section: Aysmptomatic Intracranial Aneurysmsmentioning
confidence: 99%
“…Rozenfeld and colleagues recommend screening for IA using 3 T time-of-flight MRA in all patients with ADPKD at initial diagnosis, and follow-up MRA imaging at intervals of 2–10 years, depending on patient-specific risk factors including family history of IA or SAH, hypertension, smoking, alcohol abuse, high risk professions or need for major elective surgery with potential haemodynamic instability. 53 Other experts recommend initial screening only in patients with increased risk of IA rupture defined as those with a family history of IA or SAH, a high-risk profession or those undergoing major elective surgery with potential haemodynamic instability. 42 The rationale for the latter, less-stringent screening strategy is that most detected IAs are small with low risk of rupture.…”
Section: Aysmptomatic Intracranial Aneurysmsmentioning
confidence: 99%
See 1 more Smart Citation
“…IA rupture usually occurs in patients with ADPKD at younger age than in the general population, often in patients with preserved renal function [5] . Morbidity and mortality due to SAH is also greater in ADPKD [35] with a mortality rate of 46% [36] . In the population of patients with ADPKD most common location of ruptured aneurysms is anterior circulation [19] , especially the anterior communicating artery [32] .…”
Section: Intracranial Aneurysmsmentioning
confidence: 99%
“…Some genetic diseases may also be associated with arterial wall abnormalities that may promote the formation of IC aneurysms. Among them, the most frequently encountered is the polycystic kidney disease (PCKD) [13,14]. In this specific population, the relative risk to have intracranial aneurysm is 4.4-fold higher than in the general population [15].…”
Section: Intracranial Aneurysms: Epidemiologymentioning
confidence: 99%